Potensi Aktivitas Antimikroba Serbuk Effervescent Daun Saga (Abrus precatorius L) Terhadap Jamur Candida albicans - Karmila, Mila; Idham, Syamsinar; Syalsabila, Nadifa; Ervianingsih, Ervianingsih (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Medicinal plants are plants with medicinal properties that can relieve pain, increase the body's resistance and kill disease germs. Saga leaves (Abrus precatorius L.) contain flavonoids, saponins and alkaloids which can function as antifungals. Flavonoids is a compound that has an antifungal effect so it can play a role in the healing process of canker sores caused by the fungus Candida albicans. The aim of this research is to determine innovation, antifungal activity and physical evaluation test results of saga leaf extract effervescent powder (Abrus precatorius L). Testing for the activity of the Candida albicans fungus was carried out by the agar diffusion method using disc paper. Evaluation of effervescent powder preparations includes organoleptic observations including shape, color, odor and taste. Apart from that, a flow rate test, pH test and dissolution time test were carried out. The research results showed that all preparations met the requirements based on the literature with the organoleptic test results being in powder form, green in color, and had a sweet and sour taste which did not change during the test. The pH test results for F1 were 6.25, F2 6.5 and F3 7. The flow speed test for F1 was 1.20 seconds, F2 1.24 seconds and F3 1.33 seconds. Test flow time for F1 2.31 minutes, F2 2.43 minutes and F3 2.27 minutes. Meanwhile, the antifungal test showed the diameter of the inhibition zone for the Candida albicans fungus. F1 of 17.16 mm is included in the strong category, F2 of 13.83 mm is included in the strong category and F3 10.66 mm is included in the strong category.